2006
DOI: 10.1111/j.1474-9726.2006.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of the Werner syndrome RecQ helicase in human fibroblasts

Abstract: SummaryWerner syndrome is an autosomal recessive human genetic instability and cancer predisposition syndrome that also has features of premature aging. We focused on two questions related to Werner syndrome protein (WRN) function in human fibroblasts: Do WRN-deficient fibroblasts have a consistent cellular phenotype? What role does WRN play in the recovery from replication arrest? We identified consistent cell proliferation and DNA damage sensitivity defects in both primary and SV40-transformed fibroblasts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
74
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 61 publications
7
74
0
Order By: Relevance
“…35), a DNA topoisomerase I-trapping agent (camptothecin) (20,36) and hydroxyurea (37). Silencing of WRN in cancer cells increases the chemotherapeutic activity of camptothecin (17) and CDDP (7,38). The epigenetic inactivation of WRN leads to repress WRN proteins, and increases chromosomal instability and sensitivity to chemotherapeutic drugs in cultured cells; and enhances the clinical sensitivity to camptothecin in human colorectal tumors (22).…”
Section: Discussionmentioning
confidence: 99%
“…35), a DNA topoisomerase I-trapping agent (camptothecin) (20,36) and hydroxyurea (37). Silencing of WRN in cancer cells increases the chemotherapeutic activity of camptothecin (17) and CDDP (7,38). The epigenetic inactivation of WRN leads to repress WRN proteins, and increases chromosomal instability and sensitivity to chemotherapeutic drugs in cultured cells; and enhances the clinical sensitivity to camptothecin in human colorectal tumors (22).…”
Section: Discussionmentioning
confidence: 99%
“…By using CPT, HU and PUVA, several reports show that WRN could be involved in the resolution of recombinational intermediates that arise from replication arrest or collapse (Pichierri et al, 2001;Dhillon et al, 2006;Sidorva et al, 2008). We have recently shown that WRN is involved in facilitating an ATM-mediated checkpoint in response to PUVA induced collapsed forks (Cheng et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Werner syndrome is caused by a mutation in the RecQ-like DNA helicase WRN [28,29]. WRN is believed to play an important role in the resolution of HR intermediates [30,31], and loss of function of WRN is associated with an increased frequency of deleterious recombination events [32][33][34]. In addition, heritable mutations in ATM, a protein that plays a critical role in initiating DSB repair [35], result in ataxia telangiectasia, a disease that is associated with symptoms of premature aging [17].…”
Section: Introductionmentioning
confidence: 99%